Assistance and Therapy Dogs Are Better Problem Solvers Than Both Trained and Untrained Family Dogs - Carballo, Fabricio; Cavalli, Camilla María; Gácsi, Márta; Miklósi, Ádám; Kubinyi, Enikő (Frontiers in Veterinary Science, 2020)
When faced with unsolvable or difficult situations dogs use different behavioural strategies. If they are motivated to obtain rewards, they either try to solve the problem on their own or tend to interact with a human partner. Based on the observation that in problem situations less successful and perseverant dogs look more at the humans’ face, some authors claim that the use of social strategies is detrimental to attempting an independent solution in dogs. Training may have an effect on dogs’ problem solving performance. We compared the behaviour of (1) untrained, (2) trained for recreational purposes, and (3) working dogs: assistance and therapy dogs living in families (N=90). During the task, dogs had to manipulate an apparatus with food pellets hidden inside. We measured the behaviours oriented toward the apparatus and behaviours directed at the owner/experimenter, and ran a principal component analysis. All measures loaded in one factor representing the use of the social strategy over a more problem oriented strategy. Untrained dogs obtained the highest social strategy scores, followed by dogs trained for recreational purposes, and assistance and therapy dogs had the lowest scores. We conclude that assistance and therapy dogs’ specific training and working experience (to actively help people) favours their independent and more successful problem solving performance. General training (mainly obedience and agility in this study) also increases the problem oriented behaviour.